Distributed fault estimation design of interconnected systems with external disturbances. Issue 3 (27th January 2019) - Zhang, Ke; Jiang, Bin; Shi, Peng; Pan, Jeng‐Shyang
Abstract : In this study, a new distributed fault estimation observer (DFEO) design method is proposed based on unknown input observer (UIO) for interconnected systems with external disturbances. The coupling terms among interconnected subsystems are utilised to construct DFEO. At the same time, according to the characteristics of UIO, external interference is completely decoupled to improve the robustness of fault estimation. Furthermore, the authors propose a multi‐constraint design with robust H ∞ and regional pole configurations to analyse and design gain matrices of DFEO, which can be calculated using linear matrix inequalities. Furthermore, asymptotic estimation of sensor faults is discussed with the help of DFEO. Finally, a simulation of the interconnected system is provided to illustrate the effectiveness of the proposed technique.